(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2022)
The Venezuelan philosopher Leopoldo Márquez, "Leotágoras", seeks to answer in this video a question that often bothers those who dedicate themselves to the philosophical discipline: precisely, the question: What is philosophy? is approached -with more concerns and uncertainties than definitive answers-, by Professor Márquez.